Polymyxin B-induced skin and nail hyperpigmentation in an adult - Mahendra M Kura; Poornima D Sonawane (Pigment International, 2023)
Polymyxin B is a reserve drug for resistant gram-negative bacterial infections. A rare side effect of polymyxin B is cutaneous hyperpigmentation, which characteristically involves face and neck. This is commonly reported in pediatric population. We report a case of polymyxin B-induced skin and nail hyperpigmentation and acute kidney injury in an adult patient of malignant otitis externa.